Recurrence of rare disease after kidney transplant - Farahnoosh Farnood; Seyyedeh Mina Hejazian; Kamal Boostani; Alireza Mardomi; Mohammadreza Ardalan (Society of Diabetic Nephropathy Prevention, 2023)
The incidence of chronic kidney diseases (CKDs) by rare etiologies is growing along with other CKDs. This mini-review discusses the epidemiology, pathogenesis, clinical presentation, and diagnosis of rare kidney disease recurrence after kidney transplantation (KTx) including primary hyperoxaluria (PH), adenine phosphoribosyl transferase (APRT), C3 glomerulopathy (C3 GP), and fibrillary glomerulonephritis (FGN). It was shown that PH, like acute rejection, causes delayed graft function, confusing the physicians. Moreover, C3 GP is more prevalent than FGN among kidney transplant patients. Therefore, it is necessary to monitor rare diseases (RDs) before KTx in patients with any history of bilateral nephrocalcinosis or nephrolithiasis.